2021
DOI: 10.1177/00139165211008240
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanisms of Activity-based Workspaces: A Case Study

Abstract: In recent years an increasing number of organizations have started to rethink their physical work environments and recognized the value of having activity-based workspaces (ABWs). This allows employees to choose freely between several work environments based on their specific task. There is growing debate amongst researchers about the effects of ABWs on employee behavior, but companies are still not aware of the options available or the consequences of moving to an ABW layout. This single-case, exploratory stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…Appel-Meulenbroek et al, 2011;Elsbach & Bechky, 2007). The present study also supports the findings of Eismann et al (2021), who reported that participation and regular exchanges of ideas and information increase the likelihood of developing new and useful solutions. Therefore, it is surprising that none of our interviewees referred to these issues as explicit objectives of workplace transformation, despite extensive discussions in the literature (e.g.…”
supporting
confidence: 90%
“…Appel-Meulenbroek et al, 2011;Elsbach & Bechky, 2007). The present study also supports the findings of Eismann et al (2021), who reported that participation and regular exchanges of ideas and information increase the likelihood of developing new and useful solutions. Therefore, it is surprising that none of our interviewees referred to these issues as explicit objectives of workplace transformation, despite extensive discussions in the literature (e.g.…”
supporting
confidence: 90%
“…Research supports the importance of involvement from the managers when implementing organisational and physical environment changes [ 48 ]. Studies have also highlighted the importance of leadership behaviours in relation to the implementation of different office types [ 2 , 49 , 50 ]. In addition, the COVID-19 pandemic has pushed many workers away from their offices and into their homes.…”
Section: Discussionmentioning
confidence: 99%
“…The best ratings were found for medium-sized open plan offices. Eismann and colleagues [ 50 ] studied AFOs and, according to factors related to leadership behaviours, they found new challenges for managers such as fewer contacts with employees and problems with evaluation of employee performance. However, AFOs might also support team building as managers and employees can share the same workspaces and work in greater proximity than in traditional offices [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is true that private offices clearly afford greater privacy than open-plan offices and that ABWs have fewer partitioning walls, ABWs offer more possibilities for retreating than do conventional offices. Consequently, ABWs are unique because they combine both open and closed areas (Eismann et al, 2021) JCRE 25,3 and allow employees to freely choose between these areas, meaning that individual privacy requirements are met and interactions can be controlled. Furthermore, although ABWs have been reported to have a minor negative impact on privacy, particularly high levels of autonomy offered by ABWs compared to fixed-desk offices allow employees to access different spaces to match their desired levels of privacy.…”
Section: Privacymentioning
confidence: 99%
“…Therefore, ABWs combine the advantages of open-plan and private offices while eliminating the disadvantages of both. Moreover, ABWs allow employees to choose work settings that suit their current tasks and personal needs (Eismann et al , 2021) and include open rooms for tasks that involve communication and coordination as well as more enclosed spaces for team brainstorming and concentrated tasks. Workspace options range from team areas and meeting rooms to quiet rooms and informal areas, all furnished to suit employee activities and personal preferences (Arundell et al , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%